Adductor canal block versus femoral nerve block combined with sciatic nerve block as an anesthetic technique for hindfoot and ankle surgery: A prospective, randomized noninferiority trial. Issue 52 (December 2016) - Joe, Han Bum; Choo, Ho Sik; Yoon, Ji Sang; Oh, Sang Eon; Cho, Jae Ho; Park, Young Uk
Abstract: Background: A femoral nerve block (FNB) in combination with a sciatic nerve block (SNB) is commonly used for anesthesia and analgesia in patients undergoing hindfoot and ankle surgery. The effects of FNB on motor function, related fall risk, and rehabilitation are controversial. An adductor canal block (ACB) potentially spares motor fibers in the femoral nerve, but the comparative effect on hindfoot and ankle surgeries between the 2 approaches is not yet well defined. We hypothesized that compared to FNB, ACB would cause less weakness in the quadriceps and produce similar pain scores during and after the operation. Methods: Sixty patients scheduled for hindfoot and ankle surgeries (arthroscopy, Achilles tendon surgery, or medial ankle surgery) were stratified randomized for each surgery to receive an FNB (FNB group) or an ACB (ACB group) combined with an SNB. The primary outcome was the visual analog scale (VAS) pain score at each stage. Secondary outcomes included quadriceps strength, time profiles (duration of the block procedure, time to full anesthesia and time to full recovery), patients' analgesic requirements, satisfaction, and complications related to peripheral nerve blocks such as falls, neurologic symptoms, and local anesthetic systemic toxicity were evaluated. The primary outcome was tested for the noninferiority of ACB to FNB, and the other outcomes were tested for the superiority of each variable between the groups. Results: A total of 31 patients received an ACB and 29 received an FNB. The VAS pain scores of the ACB group were not inferior during and after the operation compared to those of the FNB group. At 30 minutes and 2 hours after anesthesia, patients who received an ACB had significantly higher average dynamometer readings than those who received a FNB (34.2 ± 20.4 and 30.4 ± 23.7 vs 1.7 ± 3.7 and 2.3 ± 7.4, respectively), and the results were similar at 24 and 48 hours after anesthesia. There were no differences between the 2 groups with regard to time profiles and patient satisfaction. No complications were noted. Conclusion: ACB preserved quadriceps muscle strength better than FNB, without a significant difference in postoperative pain. Therefore, ACB may be a good alternative to FNB for reducing the potential fall risk.